Unravelling the role of unmyelinated nerve fibres in trigeminal neuralgia with concomitant continuous pain. (October 2022) - De Stefano, Gianfranco; Leone, Caterina; Di Pietro, Giuseppe; Esposito, Nicoletta; Falco, Pietro; Galosi, Eleonora; Litewczuk, Daniel; Mollica, Cristina; Truini, Andrea; Di Stefano, Giulia
Highlights: Disease duration does not differ between patients with purely paroxysmal pain and with concomitant continuous pain. Concomitant continuous pain in trigeminal neuralgia is associated with C fibre-related laser evoked potentials attenuation. Unmyelinated fibre loss may trigger abnormal activity in denervated trigeminal second-order neurons. Abstract: Objective: In this clinical and neurophysiological study, we aimed to test trigeminal nerve fibre function in patients with trigeminal neuralgia, with and without concomitant continuous pain. Methods: We enrolled 65 patients with a definite diagnosis of primary trigeminal neuralgia. Patients were grouped according to whether they experienced purely paroxysmal pain (36) or also had concomitant continuous pain (29). All participants underwent trigeminal reflex testing to assess the function of large non-nociceptive myelinated fibres and laser-evoked potentials to assess the function of small myelinated Aδ and unmyelinated C fibres. Neurophysiological examiners were blinded to the affected side. Results: The only neurophysiological abnormality distinguishing the two groups of patients was the side asymmetry of C fibre-related laser-evoked potential amplitude ( p = 0.005), which was higher in patients with concomitant continuous pain than in patients with purely paroxysmal pain (indicative of a reduced C fibre-related laser-evoked potential amplitude in the affected side of patients with concomitant continuous pain). Conclusions: Our clinical and neurophysiological study indicates that in patients with trigeminal neuralgia concomitant continuous pain is associated with unmyelinated C fibre damage as assessed with laser-evoked potentials. Significance: Our findings suggest that concomitant continuous pain is related to unmyelinated C fibre loss, possibly triggering abnormal activity in denervated trigeminal second-order neurons.